XMM-Newton observations of the supernova remnant RX J1713.7-3946 and its central source - Cassam Chenaï, G. (2004)
We present new results from the observations of the supernova remnant (SNR) RX J1713.7–3946 (also G347.3–0.5) performed in five distinct pointings with the EPIC instrument on board the satellite XMM-Newton. RX J1713.7–3946 is a shelltype SNR dominated by synchrotron radiation in the X-rays. Its emission (emission measure and photon index) as well as the absorption along the line-of-sight has been characterized over the entire SNR. The X-ray mapping of the absorbing column density has revealed strong well-constrained variations (0.4 × 1022 cm−2 ≤ NH ≤ 1.1 × 1022 cm−2) and, particularly, a strong absorption in the southwest. Moreover, there are several clues indicating that the shock front of RX J1713.7–3946 is impacting the clouds responsible for the absorption as revealed for instance by the positive correlation between X-ray absorption and X-ray brightness along the western rims. The CO and H observations show that the inferred cumulative absorbing column densities are in excellent agreement with the X-ray findings in different parts of the remnant on condition that the SNR lies at a distance of 1.3 ± 0.4 kpc, probably in the Sagittarius galactic arm, instead of the commonly-accepted value of 6 kpc. An excess in the CO emission is found in the southwest suggesting that the absorption is due to molecular clouds. A search for OH masers in the southwestern region has been unsuccessful, possibly due to the low density of the clouds. The X-ray mapping of the photon index has also revealed strong variations (1.8 ≤ Γ ≤ 2.6). The spectrum is steep in the faint central regions and flat at the presumed shock locations, particularly in the southeast. Nevertheless, the regions where the shock impacts molecular clouds have a steeper spectrum than those where the shock propagates into a low density medium. The search for the thermal emission in RX J1713.7–3946 has been unsuccessful leading to a number density upper limit of 2 × 10−2 cm−3 in the ambient medium. This low density corresponds to a reasonable kinetic energy of the explosion provided that the remnant is less than a few thousand years old. A scenario based on a modified ambient medium due to the effect of a progenitor stellar wind is proposed and leads to an estimate of RX J1713.7–3946’s progenitor mass between 12 and 16 M. The X-ray bright central point source 1WGA J1713.4–3949 detected at the center of SNR RX J1713.7–3946 shows spectral properties very similar to those of the Compact Central Objects found in SNRs and consistent in terms of absorption with that of the central diffuse X-ray emission arising from the SNR. It is highly probable that the point source 1WGA J1713.4–3949 is the compact relic of RX J1713.7–3946’s supernova progenitor.